2007
DOI: 10.1016/j.bbrc.2007.02.119
|View full text |Cite
|
Sign up to set email alerts
|

Role of homologous ASP334 and GLU319 in human non-gastric H,K- and Na,K-ATPases in cardiac glycoside binding

Abstract: Cardiac steroids inhibit Na,K-ATPase and the related non-gastric H,K-ATPase, while they do not interact with gastric H,K-ATPase. Introducing an arginine, the residue present in the gastric H,K-ATPase, in the second extracellular loop at the corresponding position 334 in the human non-gastric H,K-ATPase (D334R mutation) rendered it completely resistant to 2mM ouabain. The corresponding mutation (E319R) in alpha1 Na,K-ATPase produced a approximately 2-fold increase of the ouabain IC(50) in the ouabain-resistant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 19 publications
0
3
0
1
Order By: Relevance
“…An increase in positive charge between the lactone ring and the steroid C-16 and an increase in negative charge around the carbonyl oxygen of the lactone ring have previously been suggested to favor binding . As seen from Figure , the binding vestibule lined by the L1/2 and the L7/8 loops contains several charged residues, many of which are known from mutagenesis studies to be important for ouabain binding (indicated in red in Figure ) , . Price et al have previously suggested that electrostatic interaction of the M1−M2 loop of such charged border amino acids with other charged residues may prevent the conformational change associated with ouabain binding.…”
Section: Discussionmentioning
confidence: 90%
“…An increase in positive charge between the lactone ring and the steroid C-16 and an increase in negative charge around the carbonyl oxygen of the lactone ring have previously been suggested to favor binding . As seen from Figure , the binding vestibule lined by the L1/2 and the L7/8 loops contains several charged residues, many of which are known from mutagenesis studies to be important for ouabain binding (indicated in red in Figure ) , . Price et al have previously suggested that electrostatic interaction of the M1−M2 loop of such charged border amino acids with other charged residues may prevent the conformational change associated with ouabain binding.…”
Section: Discussionmentioning
confidence: 90%
“…The biochemical studies show a roughly similar affinity for ouabain and ouabagenin for the QN mutant of Na,KATPase. Radkov et al [30] even found a twofold lower Ki value for ouabagenin than for ouabain. In the docking experiment, ouabagenin penetrated the membrane more deeply, resulting in hydrogen bridges of the lactone ring with residues of M8.…”
Section: Discussionmentioning
confidence: 93%
“…The presence of a Glu on this position was shown to be necessary for high-affinity ouabain binding in both H,KATPases [13,14]. The binding affinity of ouabain in mutant E312R of human Na,K-ATPase [30] was much lower than that of wild-type enzyme. However, there was no difference in binding affinity when the binding of the sugarless ouabagenin was measured.…”
Section: Discussionmentioning
confidence: 97%
“…A região de interação enzimaouabaína parece envolver múltiplos resíduos chaves na subunidade  e, em menor extensão, também na subunidade  (MIDDLETON et al, 2000;POST, 2003;RADKOV et al, 2007;MIJATOVIC et al, 2007). A ouabaína liga-se seletivamente com alta afinidade à forma E 2 P e sua interação com a enzima envolve resíduos da subunidade  YATIME et al, 2011;SÁNCHEZ-RODRÍGUEZ et al, 2015), interagindo com a porção extracelular da enzima e inibindo o transporte de íons e a hidrólise de ATP (LINGREL et al, 1997;KASTURI et al, 1998;CRAMBERT et al, 2004;NESHER et al, 2007), sendo o Asp 121 o mais relevante, localizado no segmento M1 SANDTNER et al, 2011;CORNELIUS et al, 2013;LAURSEN et al, 2015).…”
Section: Figura 3 Esquema Da Estrutura Das Subunidades Da (Na + K +unclassified